Services, Resources and Benefits of the Internet Available to Academics in Ghana - Markwei, Evelyn D. (Ghana Library Journal, 2002)
The lntemet, or the Intemational network of computers, offers many services and resources which academics in Ghana can exploit to enhance their academic pursuits. The paper discusses some of these services, namely e-mail, telnet, ftp, Archie, news groups, and information discovery services like gopher, WAIS, search engines, dir ectories and information gateways . The benefits to be derived from the use of the Internet by differen t categories of academics, parti cularly lecturers, students, administrators, researchers, librarians among others, are dis cussed. The major benefit is access to information on any conceivable subject located on library catalogues, online databases, newsgroups etc. These sources abound on the Internet f or scholarly work. Other benefits are book se lection medium, acquisitions, and vir tual universities.